trans-Bis[bis(diphenylphosphanyl)methane-κ2P,P′]dichloridoruthenium(II): a triclinic polymorph - Monsuru T. Kelani; Alfred Muller; Koop Lammertsma (IUCrData, 2023)
The title compound, [RuCl2(C25H22P2)2] or [RuCl2(dppm)2] (dppm = bis(diphenylphosphanyl)methane, C25H22P2) crystallizes as two half-molecules (completed by inversion symmetry) in space group P\overline{1} (Z = 2), with the RuII atoms occupying inversion centers at 0,0,0 and 1/2, 1/2, 1/2, respectively. The bidentate phosphane ligands occupy equatorial positions while the chlorido ligands complete the distorted octahedral coordination spheres at axial positions. The bite angles of the phosphane chelates are similar for the two molecules [(P—Ru—P)avg. = 71.1°], while there are significant differences in the twisting of the methylene backbone, with a distance of the methylene C atom from the RuP4 plane of 0.659 (2) and 0.299 (3) Å, respectively, and also for the phenyl substituents for both molecules due to variations in weak C—H...Cl interactions.